2020
DOI: 10.1136/vr.105065
|View full text |Cite
|
Sign up to set email alerts
|

Development of a clinical tool to aid endotracheal tube size selection in dogs

Abstract: ObjectiveTo identify phenotypic parameters correlating with the inner tracheal diameter (ITD) and endotracheal tube size (ETS) in adult dogs and to develop a chart for ETS estimation.MethodsFive-hundred and forty-four adult dogs; 100 dogs were enrolled prospectively and 444 dogs retrospectively. Different phenotypic parameters, the ITD on latero-lateral radiography and ETS were prospectively measured in dogs that underwent general anaesthesia. The parameter correlated best with the ITD was used to develop a gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Use of thoracic radiographs for measuring internal tracheal diameter has been shown to aid reliably in selection of appropriately sized ETTs but increases radiation exposure to animals and staff, as well as costs to the client 20. The recent development of a clinical tool to allow for estimation of appropriate ETT size based on body mass following analysis of multiple phenotypic parameters may be beneficial but would require prospective clinical validation 21. Currently, there is no guaranteed method of correctly selecting ETT size, although tracheal pathology should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Use of thoracic radiographs for measuring internal tracheal diameter has been shown to aid reliably in selection of appropriately sized ETTs but increases radiation exposure to animals and staff, as well as costs to the client 20. The recent development of a clinical tool to allow for estimation of appropriate ETT size based on body mass following analysis of multiple phenotypic parameters may be beneficial but would require prospective clinical validation 21. Currently, there is no guaranteed method of correctly selecting ETT size, although tracheal pathology should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…9 A chart can be used as a clinical tool to aid appropriate endotracheal tube size selection in mesocephalic and dolichocephalic dogs. However, this tool is not accurate in brachycephalic breeds 10 and a recent study showed that some of the previously published anatomical measurements and calculations may fail to accurately predict the endotracheal tube size. 11 One reasonable approach to select the appropriate endotracheal tube size is to ensure a leak is present when the cuff is not inflated and the breathing system is pressurised at 25 cmH 2 O.…”
Section: Learning Pointsmentioning
confidence: 99%
“…Veterinarians often face challenges in selecting the appropriate ETT size for intubation in dogs because of the anatomical diversity and size differences among breeds [ 3 , 10 ]. Despite various suggested methods, no standard technique exists for accurate ETT size selection [ 7 , 10 ]. Common methods include predicting ETT size based on lean body weight [ 4 ] or externally palpating the trachea [ 7 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Common methods include predicting ETT size based on lean body weight [ 4 ] or externally palpating the trachea [ 7 , 11 ]. However, both methods present limitations: significant differences in weight among various body condition scores [ 3 , 10 ], the external and internal diameters of tracheal tubes differ significantly, and the diameter of the tracheal lumen narrows upon entering the thoracic cavity [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation